Post-chemotherapy perforation in cats with discrete intermediate- or large-cell gastrointestinal lymphoma. Issue 8 (August 2018) - Crouse, Zachary; Phillips, Brenda; Flory, Andi; Mahoney, Jennifer; Richter, Keith; Kidd, Linda
Objectives: Gastrointestinal (GI) perforation is a well described complication of GI lymphoma in people, commonly occurring within days of initiation of chemotherapy. There are no studies documenting the prevalence of GI perforation in cats with intermediate- or large-cell GI lymphoma or whether it is associated with induction of chemotherapy. The objectives of this study were to document the prevalence and timing of post-chemotherapy perforation in cats with discrete GI masses caused by intermediate- or large-cell lymphoma. Methods: Cats with a diagnosis of intermediate- or large-cell lymphoma based on cytologic or histopathologic examination of a mass lesion of the GI tract and treated with chemotherapy were identified by searching the patient record database of three large specialty referral hospitals. Cats undergoing surgical resection of a GI mass prior to chemotherapy were excluded from the study. A clinical diagnosis of GI perforation was made using ultrasound findings and analysis of abdominal fluid. Results: Twenty-three cats with intermediate- (n = 3) or large-cell (n = 20) lymphoma were included in the study. GI perforation was confirmed in 4/23 cats (17%), and occurred at 23, 56, 59 and 87 days after induction. There was no association between tumor size, the presence of hypoproteinemia or suppurative inflammation within the mass at the time of diagnosis and subsequent perforation. Post-hoc analysis revealed that the magnitude of weight loss within 15–28 days of diagnosis was greater in cats with perforation. Conclusions and relevance: In this pilot study, we found that post-chemotherapy GI perforation in cats with intermediate- or large-cell GI lymphoma occurs. Acute perforation after induction of chemotherapy was not documented. Larger prospective studies are needed to determine risk factors associated with perforation and whether surgical excision would reduce the risk of subsequent GI perforation in these patients.